Alterations of Golgi Structural Proteins and Glycosylation Defects in Cancer - Zhang, Xiaoyan (Frontiers in Cell and Developmental Biology, 2021)
As the central hub in the secretory and endocytic pathways, the Golgi apparatus continually receives the flow of cargos and serves as a major processing station in the cell. Due to its dynamic nature, a sophisticated and constantly remodeling mechanism needs to be set up to maintain the Golgi architecture and function in the nonstop trafficking of proteins and lipids. Abundant evidence has been accumulated that a well-organized Golgi structure is required for its proper functions, especially protein glycosylation. Remarkably, altered glycosylation has been a hallmark of most cancer cells. To understand the causes of Golgi defects in cancer, efforts have been made to characterize Golgi structural proteins under physiological and pathological conditions. This review summarizes the current knowledge of crucial Golgi structural proteins and their connections with tumor progression. We foresee that understanding the Golgi structural and functional defects may help solve the puzzle of whether glycosylation defect is a cause or effect of oncogenesis.